Selectivity of commonly used pharmacological inhibitors for cystathionine β synthase (CBS) and cystathionine γ lyase (CSE) - Asimakopoulou, Antonia (Blackwell Publishing Ltd, 2013)
BACKGROUND AND PURPOSE: Hydrogen sulfide (H(2)S) is a signalling molecule that belongs to the gasotransmitter family. Two major sources for endogenous enzymatic production of H(2)S are cystathionine β synthase (CBS) and cystathionine γ lyase (CSE). In the present study, we examined the selectivity of commonly used pharmacological inhibitors of H(2)S biosynthesis towards CSE and CBS. EXPERIMENTAL APPROACH: To address this question, human CSE or CBS enzymes were expressed and purified from Escherichia coli as fusion proteins with GSH-S-transferase. After purification, the activity of the recombinant enzymes was tested using the methylene blue method. KEY RESULTS: β-cyanoalanine (BCA) was more potent in inhibiting CSE than propargylglycine (PAG) (IC(50) 14 ± 0.2 μM vs. 40 ± 8 μM respectively). Similar to PAG, L-aminoethoxyvinylglycine (AVG) only inhibited CSE, but did so at much lower concentrations. On the other hand, aminooxyacetic acid (AOAA), a frequently used CBS inhibitor, was more potent in inhibiting CSE compared with BCA and PAG (IC(50) 1.1 ± 0.1 μM); the IC(50) for AOAA for inhibiting CBS was 8.5 ± 0.7 μM. In line with our biochemical observations, relaxation to L-cysteine was blocked by AOAA in aortic rings that lacked CBS expression. Trifluoroalanine and hydroxylamine, two compounds that have also been used to block H(2)S biosynthesis, blocked the activity of CBS and CSE. Trifluoroalanine had a fourfold lower IC(50) for CBS versus CSE, while hydroxylamine was 60-fold more selective against CSE. CONCLUSIONS AND IMPLICATIONS: In conclusion, although PAG, AVG and BCA exhibit selectivity in inhibiting CSE versus CBS, no selective pharmacological CBS inhibitor is currently available.